Philip Melanchthon ve Protestan ilahiyatına katkıları - Demirel, Merve (My University, 2021)
Philip Melanchthon (1497-1560), teolojik görüşleri, eserleri ve çalışmaları ile Reform döneminin öne çıkan şahsiyetlerinden biridir. Protestanların sözcüsü olarak üstlendiği önemli görevle birlikte Martin Luther’le (1483-1546) dava arkadaşlığını hayatının sonuna dek sürdürmüştür. Reform teolojisi içerisinde Lutherci öğretiler ile ilgili değişen görüşleri ile sebebiyet verdiği birçok dini ve siyasi tartışmalarla dikkatleri çekmiştir. Bu çalışmada Roma Kilisesine ve öğretilerine karşı Reform teolojisini ortaya koymak adına gerçekleştirdiği dini-siyasi faaliyetlerin yanı sıra Protestan ilahiyatına ve Alman eğitim sistemine yaptığı katkıların incelenmesi amaçlanmaktadır.

Philip Melanchthon (1497-1560) is one of the prominent figures of the Reformation period with his theological views, works and studies. Along with this important task he assumed as the spokesperson of the Protestants, he continued his fellowship with Martin Luther (1483-1546) until the end of his life. He attracted attention with his changing views on Lutheran teachings within Reformed theology, and with the many religious and political debates he caused. In this study, it is aimed to examine his contributions to Protestant theology and the German education system as well as his religious-political activities in order to reveal the Reformed theology against the Roman church and its teachings.
Keywords: Augsburg Confession; Augsburg İtikatnamesi; Din; History; Humanism; Hümanizm Philip Melanchthon; Loci Communes; Philip Melanchthon; Philip Melanchthon (1497-1560); Reform; Reformation; Religion; Tarih